Putting Crossref Metadata into Context - Fairhurst, Vanessa (Septentrio Conference Series, 2020)
See RECORDING. At Crossref, we see a future where society benefits from an open scholarly infrastructure in which all research is connected and preserved. This will enable researchers to build upon knowledge, ensure greater discoverability and dissemination of research, and aid decision-making for funders, with better evaluation and tracking of research impact. This short talk aims to deepen the understanding of the power of good metadata, by explaining how it can be harnessed to improve discoverability of content, and how it is used in the creation of collaborative tools and initiatives for the research community. Persistent identifiers (PIDs) enable clear disambiguation and persistent links to be made between researchers, their affiliations, funding and contributions. However, membership at Crossref is not just about creating identifiers for content. It is about placing that content into context and a DOI is simply one small, but important, piece of the puzzle. Crossref works in collaboration with individuals and organizations to collect extensive metadata, both bibliographic and non-bibliographic. The breadth of the metadata Crossref supports is capable of expanding over time to respond to community needs e.g. incorporating CRediT for contributor roles. It’s also key that the metadata is made openly available; comprehensive, open metadata guarantees interoperability across borders, disciplines, research outputs and organizations. It is also essential for building scalability and improving efficiency via collaborative initiatives such as the Research Organizations Registry (ROR), ORCID auto-update, and the new DataCite Commons. Crossref has minimal requirements in order to support a variety of publication practises and the schema can support a diverse range of content types and associated metadata. All of the metadata received is standardized and machine readable; the more complete this metadata is, the more likely content can be discovered and disseminated. Whenever you submit metadata to Crossref, DataCite, DOAJ or other organizations, the metadata you deposit should be accurate, complete and up to date. Accuracy is important as misspelled author names, incorrect dates, missing license information or bad URLs, undermine the usefulness of shared services, as well as being a pain for readers and authors. There remains a lack of knowledge about the value and importance of quality metadata. Machine-readable metadata and identifiers underpin both Crossref tools and services, and those developed by the wider community. I’ll detail examples of the applications of scholarly metadata to make this case, show how publishers can see the metadata they’re registering and suggest some quick fixes to getting more from your Crossref metadata.